Anisotropic Terahertz Microscopy of Protein Collective Vibrations: Crystal Symmetry and Hydration Dependence - McKinney, J.; Deng, Y. T.; Sharma, A.; George, D. K.; Markelz, A. G. (2019 44th International Conference on Infrared, Millimeter, and Terahertz Waves, 2019)
A stationary sample anisotropic terahertz microscopy technique is used to characterize the intramolecular vibrations for lysozyme. Tetragonal and triclinic crystals are compared. We find excellent reproducibility within a single crystal symmetry group. Several resonant bands are present for both symmetry groups, indicating they originate with the intramolecular vibrations and not crystal lattice phonons. Bands become more pronounced and higher frequency resonant bands begin to emerge with slight dehydration.